Penatalaksanaan Hydrotherapy Pada Anak Cerebral Palsy Spastic Quadriplegy Dengan Gangguan Kemampuan Fungsional Berdiri Dan Berjalandi Yayasan Sayap Ibu (YSI)Yogyakarta - Arifuddin, Erwin; , Agus Widodo, S.Fis, M.Kes (2015)
Background : Cerebral palsy spastic quadriplegy the term is used to describe disorders of brain development when the brain is on infancy, where this disorder is characterized with increased tendon reflexes, stretch reflexes excessive, increase muscle tone or hipercontractility muscle and clonus happens four extremity upper although lower. In this case will be found signs, symptoms and the complex problematic with main problem is the existence of postural spasticity and four extremity with activities standing and walking disorder. Aims of Research: To know the implementation of physiotherapy in the case of spastic cerebral palsy quadriplegy with functional impairment standing and walking in reducing spasticity, improve gross motor skills, as well as functional activity in the case of spastic cerebral palsy quadriplegy using aquatic therapy modalities. Result : After treatment for 6 times the obtained results at spastic assessment on right trunk T0: 3 to T6: 2, left trunk T0: 2, to T6: 2, right shoulder T0: 1, to T6: 1, left shoulder T0: 1 to T6: 1, right elbow T0: 2 to T6: 2, left elbow T0: 2 to T6: 2, right wrist T0: 2 to T6: 2, left wrist T0: 1 to T6: 1, right hip T0: 2 to T6: 2, left hip T0: 2 to T6: 2, right knee T0: 3 to T6: 2, left knee T0: 2 to T6: 2, right ankle T0: 3 to T6: 3, left ankle T0: 3 to T6: 2, increase gross motor skills T0: 83.58% to T6: 87.01%, ability fungsional T0: 58% to T6: 58%. Conclution : Aquatic therapy can reduce spasticity, increase gross motor skills (Gross Motor Function Measurement) and can increase functional activity in the caseof cerebral palsy.